2017
DOI: 10.1590/1983-40632016v4743861
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol and branch tip pruning on the flowering induction and quality of mango tree fruits

Abstract: The 'Ubá' mango tree cultivar is very important for the juice industry in the "Zona da Mata" region of the Minas Gerais State, in Brazil, but problems such as uneven flowering and low yield have discouraged producers. This study aimed at evaluating the effect of paclobutrazol, combined with branch tip pruning, on the flowering induction and quality of 'Ubá' mango tree fruits. Treatments were distributed in a 5 x 2 + 1 factorial arrangement, consisting of five paclobutrazol doses (0 g, 0.50 g, 1.00 g, 1.50 g an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
0
10
0
4
Order By: Relevance
“…In avocado (Persea americana), Brogio et al (2018) reported an increase of fruit mass and size; while, in 'Palmer' mango (Mangifera indica L.), Oliveira et al (2015) observed a reduction in the soluble solids content. Oliveira et al (2017), however, reported no effect of PBZ on the physical and chemical characteristics of 'Ubá' mango.…”
Section: Introductionmentioning
confidence: 92%
“…In avocado (Persea americana), Brogio et al (2018) reported an increase of fruit mass and size; while, in 'Palmer' mango (Mangifera indica L.), Oliveira et al (2015) observed a reduction in the soluble solids content. Oliveira et al (2017), however, reported no effect of PBZ on the physical and chemical characteristics of 'Ubá' mango.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, it also increased Alphonso cultivar [4], Miska cultivar, Mohmoudi cultivar, Totocombo culviar [8] Lechi yield [9]. In Uba mango, paclobutrazol branch tip pruning also enhanched the flowering up to 30 % [10].…”
Section: Effect Of Paclobutrazol On Flowering and Mango Yieldmentioning
confidence: 99%
“…Cultivares que possuem intensa capacidade de vegetar necessitam de maiores doses (Albuquerque et al, 2002;Oliveira et al, 2017), como é o caso das cultivares Keitt, Kent e Ubá, e dentro da mesma variedade a sensibilidade vai depender da época de aplicação, idade e nutrição das plantas. Em geral, plantas mais jovens são mais sensíveis e respondem a menores doses de paclobutrazol do que as plantas mais velhas (Albuquerque e Mouco, 2000).…”
Section: Iniciação Floral E Florescimentounclassified
“…O uso de reguladores de crescimento é essencial para o sucesso da mangicultura no Brasil, uma vez que desempenham importante função na indução floral, permitindo o escalonamento da produção durante o ano todo e obtenção de frutos de boa qualidade e quantidades que atendam a demanda interna e externa. Nas regiões semiáridas, principalmente com as cultivares de consumo in natura como a Tommy Atkins e Palmer, para as quais foram definidas doses, época e forma de aplicação, como parte das tecnologias visando à indução floral (Albuquerque e Mouco, 2005;Mouco et al, 2010;Coelho et al,2014;Oliveira et al, 2015) e em cultivar destinada a indústria de suco também foi realizado com o intuito de uniformizar a floração e a colheita (Oliveira et al, 2017). Em 2019 o escalonamento da produção de manga foi eficaz na região mineira, evitando a concentração de colheita e, consequentemente, queda nos preços (Anuário, 2019).…”
Section: Introductionunclassified